2023
DOI: 10.4102/sajbm.v54i1.3669
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of key audit matter disclosures in South African audit reports from 2017 to 2020

Abstract: Purpose: The aim of this study was to analyse the key audit matters (KAMs) being reported in South Africa by assessing 356 Johannesburg Stock Exchange (JSE)–listed entities’ audit reports from 2017 to 2020, which entailed 1424 audit reports and 2903 KAM disclosures.Design/methodology/approach: The study assessed the impact and inter-relationship of three determinants (financial year, audit firm type and industry category) on the type of KAMs disclosed, total KAMs disclosed, the number of entity- and account-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Previous studies present these effects from two different aspects. First, some research showed that due to increased business risks and uncertainty, particularly regarding going-concern issues and management misbehavior (Hategan et al , 2022), the number of disclosed CAMs has increased (Ecim et al , 2023; Kaka, 2021). Second, other studies indicate that because the social distancing outbreak imposed limitations on auditors to meet face-to-face with the board of directors, audit committee and management, as well as the gathering of sufficient evidence (Hegazy et al , 2022), therefore, negatively impact audit quality and consequently, the auditor’s ability to identify and disclose CAMs (Albitar et al , 2021).…”
Section: Results Of Bibliometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies present these effects from two different aspects. First, some research showed that due to increased business risks and uncertainty, particularly regarding going-concern issues and management misbehavior (Hategan et al , 2022), the number of disclosed CAMs has increased (Ecim et al , 2023; Kaka, 2021). Second, other studies indicate that because the social distancing outbreak imposed limitations on auditors to meet face-to-face with the board of directors, audit committee and management, as well as the gathering of sufficient evidence (Hegazy et al , 2022), therefore, negatively impact audit quality and consequently, the auditor’s ability to identify and disclose CAMs (Albitar et al , 2021).…”
Section: Results Of Bibliometric Analysismentioning
confidence: 99%
“…Therefore, several benefits and drawbacks have been mentioned for EAR in related articles. For example, some research has shown that EAR has no communicative value and informational content (Lennox et al , 2018; Köhler et al , 2020) and instead has a symbolic value (Bédard et al , 2014) because it has complex terminology and is challenging to read (Ecim et al , 2023; Abdelfattah et al , 2021). Furthermore, according to Sirois et al (2018), the disclosure of EAR caused readers to pay less attention to other parts of the financial statements.…”
Section: Results Of Content Analysismentioning
confidence: 99%
“…701 development and importance The public's trust in the integrity and reliability of audited financial reports took a major hit during the recent financial crises, prompting a closer look at the auditor's report (Vanstraelen et al, 2012). As noted by Ecim et al (2023), the auditor's report is used as a reliable reference by regulators and standard-setters in both developed and emerging nations. As a result, clients have started to question the value of audit findings that are based on the ISA.…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…One of the most recent events is ISA-701, issued by the “International Auditing and Assurance Standards Board”, which requires auditor reporting of KAM for fiscal years ending on or after 15 December 2016. During an audit of the current period’s financial accounts, the auditor will provide special attention to the following areas: IAASB (2016) and Ecim et al (2023) both back this up. KAM seeks to balance the playing field by disclosing more information to assist bridge the audit expectation gap (Segal, 2019).…”
Section: Theoretical Background and The Development Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation